APLIKASI METODE GEOLISTRIK RESISTIVITAS KONFIGURASI WENNER- SCHLUMBERGER UNTUK MENGIDENTIFIKASI LITOLOGI BATUAN BAWAH PERMUKAAN DAN FLUIDA PANAS BUMI WAY RATAI DI AREA MANIFESTASI PADOK DI KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN PROVINSI LAMPUNG - Wilyan Pratama; Rustadi Rustadi (Jurnal Geofisika Eksplorasi, 2019)
Research area is located in Padang Cermin Sun-District, Pesawaran Regency, Lampung Province. Manifestation in research area is hot water pool with surface temperatures reach 900C. Data acquisition has been done by Wenner-Schlumberger configuration with 5 acquisition line. Line 1, line 4 and line 5 have 280 meters length. Line 2 have 240 meters length and line 3 have 320 meters length with a spacing of each electrodes in each lines is every 5 meters. The objective of this research are (1)examining the geochemical contaminant and fluid types, (2)identifies the geothermal fluid based on 2D and 3D resistivity data analysis, also (3)identifies the layer of rock in Padok manifestation area based on 2D and 3D subsurface resistivity section. Subsurface lithology in research area generally divides into 4 parts. Which is hot water fluid with mean resistivity value between 1 Ωm into 3 Ωm and based on geochemistry data the fluid type is chloride water; surface sediment with resistivity value between 6 Ωm into 50 Ωm and identified as swamp sediment and alluvium sediment divides into gravels, pebbles, sands, clay and peat; Gravels, pebbles, sands, clay and peat with resistivity value between 50 Ωm into 100 Ωm; and igneous rock (andesite-basalt) with resistivity value more than 100 Ωm.